Afatinib versus cisplatin plus pemetrexed in Japanese patients with advanced non‐small cell lung cancer harboring activating EGFR mutations: Subgroup analysis of LUX‐Lung 3. Issue 9 (25th July 2015) - Kato, Terufumi; Yoshioka, Hiroshige; Okamoto, Isamu; Yokoyama, Akira; Hida, Toyoaki; Seto, Takashi; Kiura, Katsuyuki; Massey, Dan; Seki, Yoko; Yamamoto, Nobuyuki
<x xml:space="preserve">Abstract</x> In LUX‐Lung 3, afatinib significantly improved progression‐free survival (PFS) versus cisplatin/pemetrexed in EGFR mutation‐positive lung adenocarcinoma patients and overall survival (OS) in Del19 patients. Preplanned analyses in Japanese patients from LUX‐Lung 3 were performed. Patients were randomized 2:1 to afatinib or cisplatin/pemetrexed, stratified by mutation type (Del19/L858R/Other). Primary endpoint was PFS (independent review). Secondary endpoints included OS, objective response, and safety. Median PFS (data cut‐off: February 2012) for afatinib versus cisplatin/pemetrexed was 13.8 vs 6.9 months (hazard ratio [HR], 0.38; 95% confidence interval [CI], 0.20–0.70; P = 0.0014) in all Japanese patients (N = 83), with more pronounced improvements in those with common mutations (Del19/L858R; HR, 0.28; 95% CI, 0.15–0.52; P < 0.0001) and Del19 mutations (HR, 0.16; 95% CI, 0.06–0.39; P < 0.0001). PFS was also improved in L858R patients (HR, 0.50; 95% CI, 0.20–1.25; P = 0.1309). Median OS (data cut‐off: November 2013) with afatinib versus cisplatin/pemetrexed was 46.9 vs 35.8 months (HR, 0.75; 95% CI, 0.40–1.43; P = 0.3791) in all Japanese patients, with greater benefit in patients with common mutations (HR, 0.57; 95% CI, 0.29–1.12; P = 0.0966) and Del19 mutations (HR, 0.34; 95% CI, 0.13–0.87; P = 0.0181); OS was not significantly different in L858R patients (HR, 1.13; 95% CI, 0.40–3.21; P = 0.8212). Following study treatment discontinuation, most patients (93.5%) received subsequent anticancer therapy. The most common treatment‐related adverse events were diarrhea, rash/acne, nail effects and stomatitis with afatinib and nausea, decreased appetite, neutropenia, and leukopenia with cisplatin/pemetrexed. Afatinib significantly improved PFS versus cisplatin/pemetrexed in Japanese EGFR mutation‐positive lung adenocarcinoma patients and OS in Del19 but not L858R patients (www.clinicaltrials.gov; NCT00949650).